The Significance of the Uncharacteristic Sign in Article 466 of the Civil Code and Transferee Articles in the Mecelle - Bany Taha, Adala; Mousa, Nihad (Dirasat: Human and Social Sciences, 2023)
This study addresses the term of the linguistic sign in Article (466) of the Jordan Civil Code, and the articles of its explanatory memorandums representing the known sale in the Mecelle. The study discusses the significance of this sign by comparing Articles (200), (201), and (202). The purpose of the comparison is to reveal the uncharacteristic sign, which is a legal linguistic and doctrinal sign referring to what is proven through linguistic paraphrasing - where a word is used instead of another word, and both are referring to the same thing. This usage of words focuses intentionally on using a less common word in the place of a prevalent word, due to the multiplicity of the terms of one word, in order to reach a prima facie statement holding a much clearer second explanation than the first one, including the understandable aspects of the statement's meaning.